Propiedades al desgaste y corrosión de aleaciones base Ni obtenidas por depositación química - García Guerra, Josefina (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The properties of nickel-based films are investigated for which surface coatings on substrates were synthesized grade O1 tool steel and API X-52 consistent binary Ni-P alloys and ternary Ni-P-Al2O3 high phosphorus content ( 9% weight). The coatings were synthesized by a chemical technique employing electroless deposition hypophosphite as a reducing agent under controlled conditions of pH = 5.0 and 90 °C, conditions which resulted in obtaining amorphous coatings of uniform thickness of approximately 7m and 24 m. The adhesion of deposits, estimated under the VDI 3198 standard, showed films with a high degree of adhesion to the substrate and integration. By the technique of ICP was determined that the phosphorous content in the binary coating Ni-P was 9.3% weight while it adding amounts of alumina in the order of 5, 10, 15 and 20 g/L in the electrolyte solution, decreased the phosphorus content in the ternary deposits 9.0, 8.3, 7.9 and 7.3 wt% respectively, was observed that the maximum co-deposition of particle sizes was loads alumina 10 g/L, concentration at which a content is achieved 18.2% of the tank volume. The non-isothermal kinetics study showed that at temperatures greater than 300 °C crystallization of the coatings is achieved, process that modify the hardness of the coatings. Also the results showed that the addition of alumina particles and reduced phosphorus content in the tank reduces the induction time for crystallization of Ni-P phases. Through electrochemical techniques and electrochemical impedance spectroscopy polarization and reciprocal linear sliding technique, the corrosion and wear resistance was determined. Both coatings and Ni-9.3P Ni-8.3P-18.2Al2O3 significantly improve the corrosion and wear resistance of the surface of the base steel (API X-52 and O1) and acting as a barrier to oxygen diffusion to the substrate and natural lubricant.

En el presente trabajo se sintetizaron recubrimientos superficiales sobre sustratos de acero grado herramienta O1 y API X-52 consistentes de aleaciones binarias Ni-P y ternarias Ni-P-Al2O3 de alto contenido de fósforo (9% peso), por una técnica de depositación química no electrolítica empleando hipofosfito como agente reductor en condiciones controladas de pH=5.0 a temperatura de 90°C. Logrando obtener recubrimientos amorfos de espesor homogéneo de 7 a 24 m, con alto grado de adhesión estimada bajo la norma VDI 3198. Mediante la técnica de ICP se determinó que el contenido de fósforo en el recubrimiento binario Ni-P fue de 9.3% peso mientras que adicionando cantidades de alúmina en el orden de 5, 10, 15 y 20 g/L en la solución electrolítica, el contenido de fósforo disminuye a valores de 9.0, 8.3, 7.9 y 7.3 % peso respectivamente. La máxima co-depositación de partículas se obtuvo en cargas de cerámico de 10 g/L, concentración para la cual se logra un contenido de 18.2% vol en el depósito. De acuerdo al estudio cinético a temperaturas superiores a los 300°C, se presenta la cristalización de los recubrimientos; proceso que modifica la dureza de los recubrimientos. Así mismo, los resultados mostraron que la adición de partículas de alúmina y la disminución del contenido de fósforo en el depósito reduce el tiempo de inducción para la cristalización de fases Ni-P. A través de técnicas electroquímicas de espectroscopia de impedancia electroquímica y resistencia a la polarización se determinó que ambos recubrimientos Ni-9.3P y Ni-8.3P-18.2Al2O3 mejoran significativamente la resistencia a la corrosión y al desgaste de la superficie del acero base (API X-52 y O1) ya que actúan como barrera para la difusión del oxígeno hacia el sustrato y como lubricante natural.
Instituto de Investigaciones Metalúrgicas. Doctorado en Ciencias en Metalurgia y Ciencias de los Materiales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1303; info:eu-repo/classification/cti/7; IIM-D-2015-0636; Depositación autocatalítica; Resistencia al desgaste; Coeficiente de Archard